Transformasi Model Pariwisata Digital Berbasis Masyarakat Lokal di Kabupaten Enrekang: Pendekatan Model AIDDA - Muhammad Hidayat Djabbari; Dewi Sulfa Saguni; Eva Elivia (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The transformation of digital tourism has become a crucial necessity in efforts to enhance the competitiveness of tourist destinations in the modern era. This research is based on the digital tourism model, specifically in the context of community-based tourism management using the AIDDA (Attention, Interest, Desire, Decision, Action) model approach. The AIDDA model concept is an effective communication approach in the development of digital tourism, used to understand and influence the behavior of prospective tourists through digital tourism management aimed at increasing tourist interest. This study aims to analyze a suitable digital tourism model to be applied in Enrekang Regency using the AIDDA model approach. The research method used is qualitative with a descriptive approach. Data was collected through observation, in-depth interviews, and documentation, and then analyzed using the Interactive Model Analysis technique. The research results show that the AIDDA model is effective in promoting tourism destinations in Enrekang Regency through five stages: (1) Awareness, where promotion through social media increases tourists' awareness of the uniqueness of the destination; (2) Interest, influenced by positive reviews from previous visitors and supporting facilities; (3) Desire, formed by repeated promotions about the comfort and beauty of the destination's nature; (4) Decision, influenced by easy accessibility and positive reviews; and (5) Action, where tourist visits generate positive feedback that strengthens the promotion cycle. The novelty of this research lies in the application of the AIDDA model in the context of community-based tourism management